(untitled) (The Review of Diabetic Studies, 2024)
Falls among older adults represent a critical public health concern, significantly contributing to morbidity and mortality in this population. This review article examines evidence-based interventions in geriatric nursing aimed at preventing falls and enhancing mobility among older adults. The multifactorial nature of falls necessitates a comprehensive understanding of both intrinsic and extrinsic risk factors, including age-related physiological changes, cognitive impairments, environmental hazards, and chronic health conditions. Geriatric nurses play a vital role in conducting thorough risk assessments, utilizing standardized tools to identify individuals at high risk for falls. The article highlights several key intervention strategies, including tailored exercise programs that focus on strength, balance, and flexibility, which have been shown to reduce fall risk significantly. Additionally, environmental modifications, such as improving home safety through the removal of hazards and the installation of assistive devices, are discussed as essential components of a fall prevention strategy. Medication management is also emphasized, as polypharmacy can increase fall risk; therefore, regular medication reviews and patient education are critical for optimizing pharmacotherapy. Furthermore, the importance of education and empowerment for both older adults and their caregivers is underscored, as knowledge about falls prevention can lead to proactive engagement in safety measures. Interdisciplinary collaboration is essential in creating comprehensive care plans that address the diverse needs of older adults, ensuring a holistic approach to falls prevention. Ultimately, this review underscores the significance of implementing evidence-based interventions in geriatric nursing to mitigate fall risks and promote mobility. By addressing the complex interplay of risk factors and fostering a supportive environment, healthcare professionals can enhance the quality of life for older adults, enabling them to maintain independence and reduce the fear associated with falling. The findings of this review advocate for a proactive, patient-centered approach to falls prevention in geriatric nursing practice.